1990
DOI: 10.1128/aem.56.3.628-639.1990
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of manganese in a drinking water distribution system

Abstract: The deposition of manganese in a water distribution system with manganese-related "dirty water" problems was studied over a 1-year period. Four monitoring laboratories with Robbins biofilm sampling devices fitted to the water mains were used to correlate the relationship among manganese deposition, the level of manganese in the water, and the chlorination conditions. Manganese deposition occurred by both chemical and microbial processes. Chemical deposition occurred when Mn(II) not removed during water treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(75 citation statements)
references
References 14 publications
6
68
0
1
Order By: Relevance
“…The second important component found in deposits is organic matter representing 14-24%. Once again, these values were similar to values published elsewhere, which vary from 10% (Zacheus et al, 2001) to 23% (Sly et al, 1990). The organic matter most likely originates from the adsorption of dissolved organic matter escaping the water treatment plants.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The second important component found in deposits is organic matter representing 14-24%. Once again, these values were similar to values published elsewhere, which vary from 10% (Zacheus et al, 2001) to 23% (Sly et al, 1990). The organic matter most likely originates from the adsorption of dissolved organic matter escaping the water treatment plants.…”
Section: Resultssupporting
confidence: 89%
“…According to Smith et al (1996), the principal form of corrosion deposits is goethite (␣-FeOOH). The iron fraction of deposits from the study sites were in the same range as concentrations found in the literature, which vary from 23% (Sly et al, 1990) to 76% (Gauthier et al, 1996).…”
Section: Resultssupporting
confidence: 73%
“…In this study, we isolated Mn(II)-oxidizing bacteria from a conventional DW system and showed that some of the taxonomic groups are novel and some are abundant in communities of bacteria within a DW system. Although previous studies have isolated Mn(II)-oxidizing bacteria from DW systems (Schweisfurth, 1973;Sly et al, 1988;Sly et al, 1990;Cerrato et al, 2010), they have not reported that such bacteria can be abundant members of DW bacterial communities. These results contrast those of other environments where bacterial Mn(II) oxidation is prevalent but cultured Mn(II)-oxidizing bacteria were at such low abundance that they remained undetected with culture-independent methods (Dick and Tebo, 2010).…”
Section: Abundance Of Mn(ii)-oxidizing Taxa In Bacterial Communities mentioning
confidence: 99%
“…This early standard suggested that manganese in drinking water be limited to 0.05 mg/L, which was a compromise between difficulty of manganese removal and the concentration likely to be tolerated by consumers, i.e., 0.01–0.02 mg/L (USDHEW, 1962). Consumer complaints have also been associated with 0.02–0.03 mg/L manganese, leading to recommendation of lower guidelines for manganese in finished waters (Kohl & Medlar, 2007; Sly et al, 1990).…”
Section: Introductionmentioning
confidence: 99%